Multiconfiguration Dirac–Hartree–Fock radiative parameters for emission lines in Ce ii–iv ions and cerium opacity calculations for kilonovae. Issue 1 (2nd December 2020) - Carvajal Gallego, H; Palmeri, P; Quinet, P
ABSTRACT: Large-scale calculations of atomic structures and radiative properties have been carried out for singly, doubly, and trebly ionized cerium. For this purpose, the purely relativistic multiconfiguration Dirac–Hartree–Fock (MCDHF) method was used, taking into account the effects of valence–valence and core–valence electronic correlations in detail. The results obtained were then used to calculate the expansion opacities characterizing the kilonovae observed as a result of neutron star mergers. Comparisons with previously published experimental and theoretical studies have shown that the results presented in this work are the most complete currently available, in terms of quantity and quality, concerning the atomic data and monochromatic opacities for Ce ii, Ce iii, and Ce iv ions.